PERBEDAAN PENGGUNAAN METODE CERAMAH DENGAN METODE CERAMAH KOMBINASI MEDIA VIDEO TERHADAP PENGETAHUAN DAN TINDAKAN CUCI TANGAN PAKAI SABUN SISWA - Ni Kadek Rastini; ni made marwati (Poltekkes Kemenkes Denpasar, 2018)
Abstract : Handwashing with soap is able to reduce diarrhea by as much as 45%, but the use of soap for hand washing only reaches about 3% of the entire community. Counseling is very important to increase the knowledge, attitude and practice of students in maintaining their own health. The purpose of this research is to know the difference of using lecture method with lecture method combination of video media to knowledge and action of handwashing with soap at Public Elementary School 1 Dawan Klod. The type of research used is Pre Experimental research type with The One-Group Pretest-Posttest Design. The population in this research is all the students of class II and III in Public Elementary School 1 Dawan Klod with the sample of research as many as 44 respondents. Data analysis using Mann Whitney test. The result of the research shows that there is no difference in the use of lecture method with video lecture method on knowledge and action handwashing with soap students (p value of knowledge = 0,283 and action = 0,361). Suggestions that can be given to Puskesmas can use lecture and video methods to improve the achievement of health promotion goals to school children about hand washing.